Analyzing the aspects of organising paratransit services in Vilnius - Bazaras, Darius; Verseckienė, Alina (Transport, 2013)
The main objective of the paper is to analyze some aspects of organising new paratransit services in Vilnius. The main presented scientific problem is the creation of a new transportation system integrating it into the existing one. The system in Vilnius is not well adapted to people with disabilities, and therefore special transportation services for people having impaired physical mobility do not meet the requirements established for paratransit services. To solve this problem, an objective of researching demand for new services in Vilnius, the impact of such service for the whole transport system and potential problems that could arise during the organisation and installation of new services have been set. In order to create such system, one needs to know the values of specific parameters identified with the help of an expert survey. Scientific literature and information obtained from the expert survey allow making a conclusion that new paratransit services are required and can be integrated into the existing system in Vilnius.First Published Online: 03 Apr 2013